Hubungan Antara Pola Asuh Otoriter dengan Perilaku Bullying Pada Siswa SMK Swasta Kristen Harapan Sejahtera Nias - Lily Rahmadani Caniago; Nini Sri Wahyuni (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2022)
This study aims to see how big is the relationship between authoritarian parenting and bullying behavior in Harapan Sejahtera Christian Private Vocational High School students in Nias. Research with quantitative correlational type with a sample of 63 people. The authoritarian parenting scale is based on the characteristics of authoritarian parenting according to Baumrind, (Santrock 2004). namely: Parents emphasize that all parental rules must be obeyed by children, Parents act arbitrarily without being controlled by children, Children must obey and must not argue against what is ordered by parents. The bullying behavior scale is revealed based on the characteristics of bullying behavior according to Astuti (2008) which is usually aggressive both verbally and physically, wants to be popular, often causes trouble, finds fault with others, is vindictive, envious, lives in groups and controls social life at school. The results obtained a positive relationship between authoritarian parenting bullying behavior, where rxy = 0.449 with a significant p = 0.000 0.050. This means that the proposed hypothesis is accepted. The coefficient of determinant (r2) = 0.201 This shows that authoritarian parenting contributes to bullying behavior by 20.1%. It is known that the authoritarian parenting style is high with a hypothetical value of 57.5 and an empirical value of 65.73. Furthermore, bullying behavior is classified as high with a hypothetical average value of 105 and an empirical average value of 118.68.